Symbiosis preservation: Putative regulation of fatty acyl-CoA reductase by miR-31a within the symbiont harboring bacteriome through tsetse evolution - Lee, Mason H.; Hu, Gangqing; Rio, Rita V. M. (Frontiers in Microbiology, 2023)
Tsetse flies are the sole vectors of African trypanosomes. In addition to trypanosomes, tsetse harbor obligate Wigglesworthia bacteria that are essential to tsetse biology. The absence of Wigglesworthia results in fly sterility, thus offering promise for population control strategies. Here, microRNA (miRNAs) and mRNA expression are characterized and compared between the exclusive Wigglesworthia-containing bacteriome and adjacent aposymbiotic tissue in females of two evolutionarily distant tsetse species (Glossina brevipalpis and G. morsitans). A total of 193 miRNAs were expressed in either species, with 188 of these expressed in both species, 166 of these were novel to Glossinidae, and 41 miRNAs exhibited comparable expression levels between species. Within bacteriomes, 83 homologous mRNAs demonstrated differential expression between G. morsitans aposymbiotic and bacteriome tissues, with 21 of these having conserved interspecific expression. A large proportion of these differentially expressed genes are involved in amino acid metabolism and transport, symbolizing the essential nutritional role of the symbiosis. Further bioinformatic analyses identified a sole conserved miRNA::mRNA interaction (miR-31a::fatty acyl-CoA reductase) within bacteriomes likely catalyzing the reduction of fatty acids to alcohols which comprise components of esters and lipids involved in structural maintenance. The Glossina fatty acyl-CoA reductase gene family is characterized here through phylogenetic analyses to further understand its evolutionary diversification and the functional roles of members. Further research to characterize the nature of the miR-31a::fatty acyl-CoA reductase interaction may find novel contributions to the symbiosis to be exploited for vector control.